La fraude informatique : une nouvelle forme de criminalité - Dumont, Monique (Assurances, 1981)
The author cites various cases of fraud made possible by virtue of a thorough knowledge of the computer. In recent years, activities of this nature have been particularly recurrent in the U.S. and in the following article, Monique Dumont incites electronic data processing users to secure the broadest form of crime insurance possible so as to be covered in the event of a costly fraud.